(3eNJUQ NdGUI GdCKQ aj CYjGf GdbQf GdMGOi YTQs - (3eLghds; (3GdeMHj , eMeO Gejf Hf aVd Gddg Hf eMH Gddg Hf eMeO GdeMHj GdMehj, eMH GdOjf , CHh HcQ,J (B1111 (3g` s
(3ChdgG (B:s
(3ebOeI cJGH BNQ , hJHOC GdJQGLe HeG bHd JQLeI GHQGgje Hf GHQGgje Hf MSf GddbGfi s
(3BNQgG (B:s
(3JQLeI jhSa GdhVi GdbOSi GdMfai s
(3hgh eNJda ai GNJUGQI Yf GdcJGH GdPi jdjIs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B41 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B78s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B294 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B371 s
Keywords: (3GdJGQjNs